Kontroversi jihad di Indonesia : modernis vs. fundamentalis - Chirzin, M. Habib; Az, Sugiyarto (Yogyakarta : Pilar Media, 2006)
Muslim modernists' and fundamentalists' controversial interpretations regarding jihad, their influence on the concept of terrorism, and their relevance to Indonesia's religious pluralistic society and political conditions
Includes bibliographical references (p. 309-334) and index
Keywords: Jihad -- Controversial literature; Islam -- Indonesia; Islam and politics -- Indonesia; Islamic fundamentalism -- Indonesia